Problems of employment in the Republic of Uzbekistan - Axtam Nizomov; Akmal Amirov; Xamrokul Ruziev (Procedia of Social Sciences and Humanities, 2021)
Annotation.This article analyzes the issues of unemployment and poverty in our country and identifies its causes. Foreign experience was studied in order to compare the living standards of the population. Proposals have been developed on ways to increase employment and mechanisms for its implementation.